Inhibition of Casein Kinase 2 Modulates XBP1-GRP78 Arm of Unfolded Protein Responses in Cultured Glial Cells - Hosoi, Toru; Korematsu, Kenta; Horie, Naohiro; Suezawa, Takahiro; Okuma, Yasunobu; Nomura, Yasuyuki; Ozawa, Koichiro (PLOS ONE, 2012)
Stress signals cause abnormal proteins to accumulate in the endoplasmic reticulum (ER). Such stress is known as ER stress, which has been suggested to be involved in neurodegenerative diseases, diabetes, obesity and cancer. ER stress activates the unfolded protein response (UPR) to reduce levels of abnormal proteins by inducing the production of chaperon proteins such as GRP78, and to attenuate translation through the phosphorylation of eIF2α. However, excessive stress leads to apoptosis by generating transcription factors such as CHOP. Casein kinase 2 (CK2) is a serine/threonine kinase involved in regulating neoplasia, cell survival and viral infections. In the present study, we investigated a possible linkage between CK2 and ER stress using mouse primary cultured glial cells. 4,5,6,7-tetrabromobenzotriazole (TBB), a CK2-specific inhibitor, attenuated ER stress-induced XBP-1 splicing and subsequent induction of GRP78 expression, but was ineffective against ER stress-induced eIF2α phosphorylation and CHOP expression. Similar results were obtained when endogenous CK2 expression was knocked-down by siRNA. Immunohistochemical analysis suggested that CK2 was present at the ER. These results indicate CK2 to be linked with UPR and to resist ER stress by activating the XBP-1-GRP78 arm of UPR.